Remote work and teleworking as a new work scenario implemented in public management: A literature review. - et.al, Sánchez Uriarte Cristhian Jhair, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The bibliographic review in analysis, is oriented to remote work and telework in public management, in which a database of 303 publications of Scopus was used, thus obtaining the corresponding bibliometry. Then, the study proceeded to limit the most relevant papers, using a data of 98 documents between original papers and systematic literature reviews. The results that are shared allow to know the importance of the topic under study, such as the obligation of SUNEDU in readjusting the requirements for the licensing of universities that provide distance education. The importance of the expression of emotions of people who perform remote work through words in different social media, generate that people better organize their professional work with their personal life, and also, thanks to the development of ICT, smartphones allow to integrate the above mentioned and reduce time in daily activities that are performed in person. Thus, due to the pandemic, there has been an increase in publications with a wide diversity of subject areas such as social sciences, administration, computer science, engineering, psychology, medicine, among others. For the analysis of the state of the art, globalization has been identified as initial topic, followed by the impacts of teleworking, human resources management, the theory of the work process, the importance of virtual training for professional development, the analysis of the approach of Big Data in social media and the balance between personal and professional life of teleworkers.